Aspek Legalitas Dalam Pelaksanaan Perizinan Reklame Digital Oleh Pelaku Usaha di Kota Yogyakarta - Panca Dewi; Sigit Wibowo; Cecep Tedi Siswanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze implementation of digital advertising licensing in Yogyakarta City based on Regional Regulation Number 6 of 2022 and to identify challenges faced in the process. Research employs a normative juridical approach with qualitative methods. Legislative approach examines regulations such as the 1945 Constitution, Law No. 1 of 2024 on Electronic Information and Transactions, Regional Regulation No. 6 of 2022, while the conceptual approach analyzes authority, supervision, legal compliance. Bahan hukum were collected through interviews, observations, document studies, analyzed qualitatively via bahan hukum reduction, narrative presentation, conclusion drawing. The findings indicate digital advertising licensing in Yogyakarta City has a robust legal foundation, but implementation is hindered by low compliance among business actors (31.9% of digital advertisements were unlicensed in 2024), complex procedures, and inadequate coordination among agencies such as DPMPTSP, BPKAD, and Satpol PP. Key challenges include unclear technical regulations, overlapping authorities, limited monitoring technology, and low legal awareness among business actors due to high licensing costs. Study recommends revising Regional Regulation, digitizing licensing system through OSS, strengthening inter-agency coordination, conducting socialization programs to enhance compliance, thereby supporting orderliness, city aesthetics, increased local revenue, legal certainty. These measures can strengthen Yogyakarta’s efficient and harmonious digital advertising governance.